Difference Equations and Sharing Values Concerning Entire Functions and Their Difference - Zhiqiang Mao; Huifang Liu (Abstract and Applied Analysis)
The value distribution of solutions of certain difference equations is investigated. As its applications, we investigate the difference analogue of the Brück conjecture. We obtain some results on entire functions sharing a finite value with their difference operators. Examples are provided to show that our results are the best possible.